The Effect of The Audit Committee, Company Size and Audit Tenure on Earnings Management - Satiman, Satiman; Novia, Kota (EAJ (Economic and Accounting Journal), 2023)
This study aims to empirically test and empirically prove audit committees' effectiveness, firm size, and tenure audits on earnings management. The population in this study are companies in the goods and consumption industry sector listed on the Indonesia Stock Exchange. The sample selection method in this study used a purposive sampling method. This study's total number of samples was 15 goods and industrial consumption companies listed on the Indonesia Stock Exchange during the 5-year observation period (2017-2021). The analytical tool for testing the hypothesis is EViews version 10. The data analysis method uses descriptive statistical analysis, panel data test, classic assumption test, and hypothesis test. The results of this study indicate that the audit committee, firm size, and tenure audit simultaneously influence earnings management. While the partial firm size and audit tenure do not affect earnings management, the audit committee affects earnings management.